1988
DOI: 10.1111/j.1423-0410.1988.tb04683.x
|View full text |Cite
|
Sign up to set email alerts
|

High‐Titer, High‐Thermal‐Amplitude Cold Autoagglutinin Not Associated with Hemolytic Anemia

Abstract: An example of an unusual cold autoagglutinin is reported. The antibody was monoclonal IgMKappa able to fix complement, and, in the presence of albumin, had both a high titer (greater than 4,096 at 4 degrees C) and a wide thermal range (4-37 degrees C). The patient was closely followed over a 3-year period with no evidence of hemolysis ever documented, despite a persistently positive direct antiglobulin test and the presence of the cold autoagglutinin. In contrast to previous reports regarding cold-agglutinin d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…It is unclear why a powerful warm autoagglutinin did not cause obvious hemolytic anemia. Similar cases of cold agglutinins of high‐thermal range without hemolysis have been reported and remain unexplained . Autoantibodies of IgM class may cause in vivo RBC agglutination.…”
Section: Discussionmentioning
confidence: 54%
“…It is unclear why a powerful warm autoagglutinin did not cause obvious hemolytic anemia. Similar cases of cold agglutinins of high‐thermal range without hemolysis have been reported and remain unexplained . Autoantibodies of IgM class may cause in vivo RBC agglutination.…”
Section: Discussionmentioning
confidence: 54%
“…Thus, although his anti‐HI autoantibody agglutinated A1 RBCs at 30°C in the presence of albumin, it did not appear to cause clinically significant hemolysis of his endogenous A1 RBCs. Although in vitro thermal amplitude screening tests that use albumin enhancement are highly sensitive and specific for clinically significant cold agglutinins, 2 in vivo hemolysis may not always be observed 21 . Presumably, his RBCs were protected from hemolysis by the reduced level of H antigen that is expected on A1 RBCs.…”
Section: Discussionmentioning
confidence: 99%
“…Four patients were described who had high‐titer (>1000) cold agglutinins that were not reactive at 30°C and who had no hemolytic anemia. Sniecinski and coworkers 26 described a case that showed that this correlation was not always true. Their patient, who had a high‐titer, high‐thermal‐amplitude cold autoantibody, was followed for 3 years and showed no signs of hemolytic anemia.…”
Section: Discussionmentioning
confidence: 99%